2022
DOI: 10.21203/rs.3.rs-1898117/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A longitudinal characterization of the seminal microbiota and antibiotic resistance in yearling beef bulls subjected to different rate of gains using 16S rRNA gene sequencing and culturing

Abstract: Background: Increasing evidence supports the existence of a microbial community in bovine semen, and that this seminal microbiota may influence not only the male fertility but also female reproduction. In this study, we evaluated the seminal and fecal microbiota in yearling beef bulls fed a common diet to achieve moderate (1.13 kg/d) or high (1.80 kg/d) rates of weight gain. Semen samples were collected on days 0 and 112 of dietary intervention (n = 19/group) as well as post-breeding (n = 6/group) using electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Fusobacteriota (36.3%), Bacteroidota (30.4%), Firmicutes (17.1%), and Actinobacteriota (14.9%) were identified as the major phyla. Our qPCR results showed that the overall mean total bacterial concentrations in the semen samples collected at d 112 and post-breeding was estimated to be about 1.1 billion 16S rRNA gene copies per ml semen ( Webb et al, 2022 ). The mean sperm cell concentration from these semen samples was 30 million per ml semen which was estimated by computer-assisted sperm analysis (CASA; Crouse et al unpublished data).…”
Section: Male Reproductive Tract Microbiomementioning
confidence: 97%
See 2 more Smart Citations
“…Fusobacteriota (36.3%), Bacteroidota (30.4%), Firmicutes (17.1%), and Actinobacteriota (14.9%) were identified as the major phyla. Our qPCR results showed that the overall mean total bacterial concentrations in the semen samples collected at d 112 and post-breeding was estimated to be about 1.1 billion 16S rRNA gene copies per ml semen ( Webb et al, 2022 ). The mean sperm cell concentration from these semen samples was 30 million per ml semen which was estimated by computer-assisted sperm analysis (CASA; Crouse et al unpublished data).…”
Section: Male Reproductive Tract Microbiomementioning
confidence: 97%
“…Our group recently characterized seminal microbiota in yearling beef bulls subjected to different rates of weight gain using 16S rRNA gene sequencing, qPCR, and culturing ( Webb et al, 2022 ; Table 1 ). In this study, semen samples were collected on days 0 and 112 of dietary intervention ( n = 38 per time point) as well as post-breeding ( n = 12).…”
Section: Male Reproductive Tract Microbiomementioning
confidence: 99%
See 1 more Smart Citation